Kedudukan Dewan Komisaris Sebagai Wakil Pemerintah Daerah Provinsi Riau dalam Melakukan Pengawasan Bank BUMD di Kota Pekanbaru - Irfansyah (Jurnal Hukum Respublica, 2020)
The purpose of this study is to explain the position of the Board of Commissioners as the Riau Government in conducting Supervision at Bank BUMD according to the provisions of Law Number 40 Year 2007 regarding Limited Liability Company. The type of this research is sociological law research, conducted by empirical approach by examining the formulation of the problem to be examined as well as providing an overview and analysis of the Position of the Board of Commissioners as the Representative of the Riau Government in conducting Supervision at Bank BUMD in Pekanbaru City based on Law Number 40 Year 2007 on Limited Liability Compan. From the results of this study can be taken several conclusions, among others, as follows: a. The Board of Commissioners shall have the duty of oversight for the interests of the Company and in accordance with the purposes and objectives of the Company for its management policy, general management of the Company and the Company's business, and advises the Board of Directors. b. The Commissioner is personally liable for the loss of the Company if the person is guilty or negligent in performing his duties.c. The Board of Commissioners shall be jointly and severally liable with all members of the Board of Directors, if the company.